Synthesis and characterization of NaYGdF4 upconversion nanoparticles and an investigation of their effects on the spectroscopic properties of two phthalocyanine dyes - Taylor, Jessica Mary (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
Sphere and star shaped NaYGdF4:Yb/Er(Tm) upconversion nanoparticles were successfully synthesized utilizing a methanol assisted thermal decomposition approach and their chemical, spectroscopic and fluorescence properties were fully characterized. In addition, their influence on the spectroscopic and fluorescence properties of two phthalocyanines (Pcs) (unsubstituted tetrathiophenoxy phthalocyanine (H2Pc) and aluminium octacarboxy phthalocyanine (Cl)AlOCPc) was investigated. Upconversion nanoparticles were found to produce characteristic upconversion fluorescence emissions in the blue, green, red and NIR regions and were also shown to possess paramagnetic properties. Simple mixing with an H2Pc in toluene was found to exert no change on the spectroscopic or fluorescence properties of the Pc while covalent conjugation to a (Cl)AlOCPc resulted in a large Q band blue shift accompanied by a decrease in fluorescence lifetimes in DMSO. The red light excitation mediated singlet oxygen generation of the H2Pc mixed with upconversion nanoparticles was investigated and singlet oxygen fluorescence lifetimes were found to decrease in the presence of the nanoparticles. Upconversion mediated singlet oxygen generation, by way of resonance energy transfer to the Pc, was also attempted using 972 nm excitation; however, no singlet oxygen was detected utilizing singlet oxygen NIR emission detection. Pending further work using alternative singlet oxygen detection methods, this suggests that while upconversion nanoparticles possess excellent fluorescent imaging capabilities, they are relatively inefficient in inducing singlet oxygen production simply when mixed with phthalocyanines. Despite this, by combining phthalocyanines and upconversion nanoparticles, we present a system capable of: multimodal imaging, using both upconversion and phthalocyanines emissions, singlet oxygen generation, via direct excitation of the phthalocyanine with red laser light, and, possibly, magnetic resonance imaging, as a result of doping the upconversion nanoparticles with Gd3+ ions.
Keywords: Uncatalogued